1974
DOI: 10.1111/j.1432-1033.1974.tb03765.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Carboxy‐Terminal Degradation of the αA Chain of α‐Crystallin

Abstract: Chromatographically and electrophoretically homogenous preparations of αA‐chains of α‐crystallin actually contain two types of chains. Beside the normal αA‐chain, 173 residues in length, a variable proportion of a shortened chain is present, which lacks five residues at the C‐terminal end. This chain, referred to as αA1–168, is found in all mammalian species thus far investigated. The two electrophoretic forms of the αA‐chain, αA1 and αA2, both exhibit the shortened version. The proportion of shortened αA‐chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…My calculations show that, at an approximately stoichiometric concentration of enzymes to a-crystallin, heat aggregation is completely suppressed. This was the case with GroEL and a-glucosidase (20 (45)(46)(47)(48)(49)(50)(51)(52). The effects of all of these modifications on the function of a-crystallin in the lens and other tissues is yet to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…My calculations show that, at an approximately stoichiometric concentration of enzymes to a-crystallin, heat aggregation is completely suppressed. This was the case with GroEL and a-glucosidase (20 (45)(46)(47)(48)(49)(50)(51)(52). The effects of all of these modifications on the function of a-crystallin in the lens and other tissues is yet to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…However, beside the normal Ai, AZ, Br and Bz bands some additional polypeptides were present as already observed by others [9-111. Studies on bovine a-crystallin have shown that in this species such additional bands, especially pronounced in the adult lens nucleus, represent postsynthetic modifications of the primary gene products AZ and Bz [5,12] . cu-Crystallin from normal and cataractous lenses showed essentially the same pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Several truncation products have been characterized. aA-crystallin is processed age-dependently by cleavage at various amino acids in the C-terminal half of the molecule resulting in the polypeptides aA(1-172) [177], aA(1-169), aA(1-168) [178], aA(1-151) [179] and aA(1-101) [180].…”
Section: Truncationmentioning
confidence: 99%